2007
DOI: 10.1210/en.2006-0884
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Steroidogenic Factor Enhances Angiotensin II-Stimulated Aldosterone Release by Bovine Zona Glomerulosa Cells

Abstract: Endothelium-derived steroidogenic factor (EDSF) is an endo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…18,19 Alternatively, Ang IV and Ang (1-7) did not stimulate aldosterone production in bovine adrenal zona glomerulosa cells. 16 Because the primary Ang II metabolite from the cortical arteries was Ang (1-7), we predict that vascular Ang II metabolism would reduce Ang II stimulation of steroid hormone release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Alternatively, Ang IV and Ang (1-7) did not stimulate aldosterone production in bovine adrenal zona glomerulosa cells. 16 Because the primary Ang II metabolite from the cortical arteries was Ang (1-7), we predict that vascular Ang II metabolism would reduce Ang II stimulation of steroid hormone release.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Although Ang III is equipotent to Ang II in stimulating steroidogenesis, 18,19 Ang IV and Ang (1-7) are inactive. 16 Ang II metabolism by intact adrenal arteries has not been evaluated, and, thus, the consequence of this metabolism on adrenal arterial vascular tone has not been characterized.…”
mentioning
confidence: 99%
“…173,209 ALDO also increases vascular endothelial stiffness, leading to endothelial dysfunction, which favors proteinuria. 210214 According to recent studies, the adverse effect of AT II appears to be dependent on the contribution from ALDO. 215217…”
Section: Cardiac and Renal Abnormalities Related To Ras Overactivitymentioning
confidence: 99%
“…The study also includes in-vitro experiments to assess formation of Ang 1-7 by ACE2 on adrenal cells. Previous studies have shown that small amounts of Ang 1-7 can be synthesized from Ang II, in adrenocortical cells [5,6] but the contribution of ACE2 to this process is unknown. Experiments by Caroccia et al suggest that local ACE2 does not contribute significantly to the synthesis of Ang 1-7 in adrenal tissues as basal Ang 1-7 production, in an adrenal adenocarcinoma cell line (NCI-H295), is not affected by an ACE2 inhibitor.…”
mentioning
confidence: 99%